Wastewater Management in Developing Counties: Nutrient Input Control in Coastal Cities - Kathijotes, Nicholas (My University, 2012)
The management and treatment of sludge in developing countries, from on-site sanitation systems has neither been addressed by problem holders nor by researchers. All septic tanks need to be desludged regularly in order to maintain a certain level of treatment efficiency and minimize ecological and eventual marine pollution incidences. Practices followed in developing countries are discussed and lessons learned are emphasized for promoting a sustainable community development. Stakeholder identification and participation and their cooperation thorough the process, as well as new regulations on service provision and management rocedures are addresses in this study.
Keywords: Wastewater; Coastal zones; Fecal sludge; Nutrient control; Septage; Coastal zones; Fecal sludge; Nutrient control; Septage